Faktor Faktor yang Mempengaruhi Kegagalan Pemberian ASI Ekslusif di PMB Yunita Vero AMD KEB Bandar Lampung - Mayang Novita Sari; Sunarsih Sunarsih; Nurul Isnaini (Malahayati Nursing Journal, 2026)
ABSTRACT The achievement of breast milk, which is still far below the national target, is a sign that mothers' awareness of providing breast milk still needs to be increased. Exclusive breastfeeding in Lampung Province in 2020 was 59.4%,while in Bandar Lampung City, exclusive breastfeeding in 2021 was 61.93%. The aim of this research is to determine the factors that influence the failure of exclusive breastfeeding in Independent Midwife Practices. (PMB) Yunita Vero AMd.Keb Bandar Lampung 2023. Quantitative research type, cross sectional design, population and sample were 40 breastfeeding mothers, research conducted in August 2023. Data analysis used univariate and bivariate using the chi square test. Of the 40 respondents with higher education (SMA to S1) there were 23 respondents (57.5%), the economy with low income Rp. 2,991,349.35 (UMK) was 22 respondents (55.0%), the environment was supportive for20 respondents (50.0%), and exclusive breastfeeding failure in the non-exclusive category was 22 respondents (55.0%). There is a relationship between education and failure to provide exclusive breastfeeding with a p-value of 0.001 (0,05). There is an economic relationship to the failure of exclusive breastfeeding with a p-value of 0.001(0,05). There is a relationship between the environment (support) and the failure to provide exclusive breastfeeding with a p-value of 0.004 (0,05). Advice for mothers and the community provides insight into the importance of giving exclusive breastfeeding to babies aged 0-6 months by understanding the benefits and importance for both mother and baby. Keywords: Failure of Exclusive Breastfeeding, Education, Economy, Environment. ABSTRAK Pencapaian ASI yang masih jauh di bawah target Nasional, merupakan tanda bahwa kesadaran para ibu dalam memberikan ASI masih perlu ditingkatkan. Pemberian ASI Eksklusif di Provinsi Lampung pada tahun 2020 sebesar 59,4%, sedangkan di Kota Bandar Lampung pemberian ASI Eksklusif pada tahun 2021 adalah sebesar 61,93%. Tujuanpenelitian ini adalah diketahui faktor-faktor yang mempengaruhi kegagalan pemberian ASI eksklusif di Praktik Mandiri Bidan (PMB) Yunita Vero AMd.Keb Bandar Lampung Tahun 2023. Jenis penelitian kuantitatif, rancangan cross sectional, populasi dan sampel adalah ibu menyusui sebanyak40 responden, penelitian dilakukan bulan Agustus 2023. Analisa data menggunakan univariate dan bivariate menggunakan uji chi square. Dari 40 responden pendidikan tinggi (SMA s/d S1) sebanyak 23 responden (57,5%), ekonomi dengan pendapatan rendah Rp2.991.349,35 (UMK) sebanyak 22 responden (55,0%), lingkungan mendukung sebanyak 20 responden (50,0%), dan kegagalan ASI eksklusif dengan katergori tidak eksklusif sebanyak 22 responden (55,0%). Ada hubungan pendidikan terhadap kegagalan pemberian ASI Eksklusif dengan nilai pvalue 0,001 (0,05). Adahubungan ekonomi terhadap kegagalan pemberian ASI eksklusif di dengan nilai p-value 0,001 (0,05). Ada hubungan lingkungan (dukungan) terhadap kegagalan pemberian ASI eksklusif dengan nilai p-value 0,004 (0,05). Saran bagi ibu dan masyarakat memberikan wawasan pentingnya pemberian ASI eksklusif kepada bayi usia 0-6 bulan dengan mengertimanfaat dan pentingnya bagi ibu maupun bayi. Kata Kunci: Kegagalan Asi Ekslusif, Pendidikan, Ekonomi, Lingkungan.